IN VITRO RESPONSE OF TRACHEAL SMOOTH MUSCLE FROM HYPERRESPONSIVE GUINEA PIGS TO CELIPROLOL - Shaukat, Asma; Kazmi, Sumera; Shaheen, Robina (Journal of Ayub Medical College Abbottabad, 2012)
Background: The use of β-blockers is limited by adverse effects such as bronchospasm in asthmatics. Third generation β-blockers such as celiprolol may show better respiratory tolerability because they lack β-blocker induced broncho-constriction. Method: Effect of celiprolol on the histamine induced contraction of tracheal muscle strips prepared from ovalbumin-sensitised guinea pigs was studied. Using oxygenated Krebs-Henseleit solution as the nutrient medium, the trachealis muscle activity was measured with isometric force displacement transducer and recorded on 4-channel Oscillograph. Result: Celiprolol 10-4 M shifted the concentration-response curve of histamine downwards and to the right. Mean of amplitude of contraction, percent responses and deviations when compared with the control group were significantly different (p<0.05). Conclusion: Celiprolol antagonised histamineinduced contractions of tracheal muscle of guinea pigs. So it may be considered safe in patients with asthma. However, further clinical evaluation and exploratory work is required. Keywords: Celiprolol, Histamine, Chronic Obstructive Airway Disease (COAD), Tracheal muscle